Політико-правові чинники розвитку ринку продуктів харчування для дітей шкільного віку - Коноваленко, Анастасія Сергіївна; Коноваленко, Анастасия Сергеевна; Konovalenko, Anastasiia (My University, 2019)
UK: У статті наведено аналіз політико-правових чинників макромаркетингового середовища ринку продуктів харчування для дітей шкільного віку, результати огляду положень чинного законодавства та змісту національних програм, що стосуються сфери управління безпекою харчування дітей. Визначено політико-правові чинники, які підлягають подальшій оцінці з огляду на зазначення потенційних загроз та висвітлення альтернативних можливостей подальшого розвитку ринку продуктів харчування. Наведено аналіз основних політичних ризиків, які формують діапазон можливих змін у напряму посилення безпеки харчування у дитячому сегменті ринку. Доведено, що на стан системи управління безпекою харчування дітей негативно впливає низка застарілих норм, які потребують перегляду. Зазначено вплив високого рівня корумпованості у сфері державних закупівель, що призводить до погіршення якості їжі та організації харчування дітей у загально-освітніх закладах. RU: В статье приведены анализ политико-правовых факторов макро-маркетингового окружения рынка продуктов питания для детей школьного возраста, результаты обзора норм действующего законодательства и национальных программ, касающихся сферы управления безопасностью питания детей. Определены политико-правовые факторы, которые подлежат оценке для определения потенциальных угроз и поиска альтернативных возможностей развития рынка продуктов питания. Приведен анализ политических рисков, которые формируют диапазон изменений по усилению безопасности питания в детском сегменте рынка. Доказано, что на состояние системы управления безопасностью питания детей влияют устаревшие нормы, требующие пересмотра. Отмечено влияние высокого уровня коррупции в сфере государственных закупок, что обуславливает ухудшение качества еды и организации питания детей в общеобразова- тельных учреждениях. EN: Ensuring the safety of children's nutrition is an important function of the state and an important element of social policy. The article provides an analysis of the political and legal factors of the macro-marketing environment of the food market for schoolchildren, the results of a review of current legislation and national programs related to the management of child nutrition safety. It is stated that the organization of food in educational institutions belonging to or transferred to the territorial communities belongs to the powers of local self-government bodies and local executive authorities.According to the requirements of the current legislation, the founders (owners), the heads of these institutions and organizations (enterprises) who are responsible for the organization of the nutrition of children in educational institutions, regardless of subordination, types and forms of ownership, for the material and technical condition of the cafeteria or the buffet. provide food for children. Political and legal factors that are subject to assessment to identify potential threats and search for alternative opportunities for the development of the food market are identified. It is concluded that the state provides social protection for the interests of certain categories of children, including primary school children, orphans, children and low-income families. Attention is focused on the impact of European integration processes on the state of the food market for children. It is noted that the prolonged armed conflict in the east of Ukraine hinders the development of the food market for children. Ensuring proper nutrition of children is a strategic task of the state. The analysis of political risks that form the range of changes to strengthen food safety in the children's market segment is given. It has been proved that outdated norms that require revision affect the state of the child nutrition safety management system. The impact of a high level of corruption in public procurement was noted, which leads to a deterioration in the quality of food and the organization of children's nutrition in educational institutions.
Политико-правовые факторы развития рынка продуктов питания для детей школьного возраста
Political and legal factors of development of food market for school children
Keywords: ринок; маркетинг; харчування дітей; політико-правові чинники; макросередовище ринку; продовольча безпека; рынок; маркетинг; питание детей; политико-правовые факторы; макроокружение рынка; продовольственная безопасность; market; marketing; children's nutrition; political and legal factors; macro-environment of the market; food security